Pengaruh Budaya Organisasi, Tingkat Kedisiplinan Karyawan, Organizational Citizenship Behavior terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Intervening - Melati Cahya Qur'ani; Qristin Violinda; Shofif Sobarudin Akbar (Green Economics Review, 2025)
This study aims to examine the influence of organizational culture, employee discipline, and Organizational Citizenship Behavior (OCB) on employee performance through job satisfaction among employees of Notary & PPAT offices in Semarang City. A quantitative research method was used. The population consists of employees working in Notary & PPAT offices in Semarang, with a sample size of 149 respondents selected using a snowball sampling technique, which is a type of non-probability sampling. Data were analyzed using SmartPLS. The findings reveal that organizational culture (X1), work discipline (X2), and OCB (X3) have a positive and significant impact on employee performance (Y) and job satisfaction (Z). Furthermore, job satisfaction (Z) significantly affects employee performance (Y), and mediates the relationship between organizational culture, work discipline, and OCB with employee performance. The results also show that employee performance and job satisfaction received the lowest average ratings in the respondent’s answers. The background of this research highlights that many employees remain dissatisfied with their jobs due to low income and excessive work pressure, which contributes to decreased performance and limits their ability to work optimally. Therefore, it is important to establish a clear working system and conduct regular evaluations to improve employee performance and satisfaction.